Microscopic evaluation of the manubriosternal joint (Research, Society and Development, 2022)
Introduction: The anatomical, histological and functional classification of the manubriosternal joint is a subject that has caused disagreement among authors. It is considered a secondary cartilaginous joint (symphysis), in which bone union occurs through fibrocartilage, and has been classified as primary cartilaginous joint (synchondrosis), in which bone union occurs through hyaline cartilage. The objective of the project is the macroscopic and microscopic evaluation of the manubriosternal joint in previously dissected sternum belonging to the anatomy laboratory of the University of Uberaba, in order to identify the tissues that make up the bone union, classify them and compare them with what has already been described in the bibliography. Methodology: fragments of 6 manubriosternal joints from anatomical specimens were selected and slides of these fragments were made, which were stained with hematoxylin and eosin, picrosiriushematoxylin and gomori's trichrome. Subsequently, the slides were analyzed under an optical microscope to identify the tissue responsible for bone union. Result: After analyzing the slides made, we found that all bone unions occurred through fibrous cartilage and, therefore, all were considered secondary cartilaginous (symphysis). Conclusion: Despite the divergence in the literature, we concluded that the manubriosternal joint is classified as a symphysis.